BIOCHEMICAL EFFICACY OF A CHITOSAN AND WHEY POWDER COMBINATION ON VITAMIN AND MINERAL UTILIZATION IN COBB 500 BROILER CHICKS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article experimentally evaluated the effect of a combination of chitosan and whey powder on vitamin-mineral metabolism, intestinal morphology, antioxidant protection, blood biochemistry and productivity indicators in broiler chicks of the Cobb 500 cross. The experimental model was developed based on the doses given in international and local scientific sources, normative indicators of broiler physiology, and works published by Rakhmonov F.Kh. In the research design, 100 one-day-old Cobb 500 chicks were divided into 4 groups: control, groups receiving 40 mg/head, 60 mg/head and 80 mg/head of the chitosan-whey complex. According to the model results, at a dose of 80 mg/head, live weight gain compared to the control was 11.8%, apparent calcium reduction was 7.4 percentage points, phosphorus reduction was 6.2 percentage points, glutathione level increased by 38.9%, and malondialdehyde decreased by 28.6%. Feed conversion ratio improved from 1.78 to 1.61. The results show that the combination of chitosan and whey enhances metabolic efficiency in broiler chickens by increasing intestinal absorption surface area, reducing pathogenic microflora pressure, increasing the bioavailability of mineral ions, and reducing oxidative stress.